Modeling base to design controlled release fertilizer matching with nitrogen uptake of rice plant - Trinh, T.H. (AIChE, 2015)
Controlled release fertilizer (CRF) has attracted a lot of interested because of its advantages on ecosystem in terms of enhancement of nutrient utilization and reducing nutrient loss from leaching, volatilization. As for supplement nutrient from fertilizer is synchronized with nutrient demand, surplus available plant nutrients in soil are avoided. Modeling, therefore, becomes a necessary tool to predict release behavior and determine good CRF design that match the nutrient requirement from the plants. The present study proposes a method to predict/design CRF parameters matching nitrogen uptake from rice plant based on multi-diffusion model. According to our results, there are several choices to manufacturer, because the design solution is not unique. However, the most stable design can be obtained as analyzed standard error (SE) variation against coating thickness for different granule sizes. In this case, the optimum urea radius and coating thickness are 1.125 mm and 115 mm, respectively. In addition, the simulated release curve can match the nitrogen uptake from rice plant according to our optimal parameters. Copyright Â© American Institute of Chemical Engineers. All rights reserved.